Analyzing Realities, Struggles and Challenges of the Self-Determination Right: A Study of Ahwazi People and Non-Persian Nations in Iran: Analizando realidades, luchas y desafíos al derecho de libre determinación: Un Estudio sobre el Pueblo Ahwazi y las Naciones no persas en Irán - Hetteh, Abdulrahman (Revista Tribuna Internacional, 2024)
This article examines the persistent advocacy of the Ahwazi people in Iran for their right to self-determination within the framework of international law, amidst historical and contemporary grievances. Focusing on Ahwazi Arabs, it challenges prevailing perceptions of the Persian majority and scrutinizes issues of group identity, discrimination, and minority rights. By critically evaluating League of Nations and the United Nations’ legal frameworks, in relation to the Ahwazi people and non-Persian nations in Iran, it reveals shortcomings in addressing their national aspirations and rights. Furthermore, it scrutinizes the Persian-centric system in Iran, highlighting the systemic marginalization of ethnic minority rights within academic discourse and emphasizing the necessity to recognize Iran’s diverse cultures and nationalities. Scholars and activists can contribute to a more nuanced understanding of the struggles and aspirations of non-Persian nations, including the Ahwazi people, within the ambit of international human rights law. This article seeks to fill existing gaps in the literature by amplifying Ahwazi perspectives, suggesting future research directions, and advocating for international backing for their quest for justice and self-determination.